Misturas de biodiesel de soja, com aditivação e variação do ponto de avanço, em um motor de injeção direta - Nietiedt, Gustavo Heller (2010)
The diesel fuel is used widely in the country and the world. Moreover, growing environmental awareness leads to a larger demand for renewable energy resources. The pioneering in the use of ethanol makes Brazil also bears some conditions to move quickly to consolidate the use of the biodiesel in larger scales, in the replacement or as a blend with mineral diesel in diesel engines. Thus, this work evaluated by tests on a dynamometer bench, the performance of an agricultural tractor equipped with direct injection engine using different blends of soybeans methyl biodiesel. Also, it was analyzed the influence of additives to improve the performance, and it was used two positions of injection timing, one of them original and the other advanced. The best results were obtained using the B10 fuel for all performance parameters measured (torque, power and specific fuel consumption). For the variable torque this proportion presented values 0.4% higher than the values presented by the B5 proportion, being that, for the variable power, the values of B10 fuel were higher 0.2% compared to B5, making the differences between the fuels virtually inexpressive. Already the B100 fuel presented the lowest performance in torque, power and specific fuel consumption. For the specific fuel consumption, this proportion presented the highest values, 10% higher than the values for B10 fuel. Regarding the use of additives and the variation of the initial injection timing it was not identified significance in the results. For these test conditions, where tests were realized in a tractor model 1986, equipped with an engine with 3000 hours of work, it is possible to observe that there is the possibility of use higher concentrations of biodiesel added to mineral diesel without the necessity of engine modifications. However, it is perfectly normal that happened a performance fall under the use of higher levels of soybeans methyl biodiesel. Thus, should be consider the use of higher proportions of biodiesel added to diesel commercial, doing an analysis of the economic viability inherent of biofuels use.